UNDERSTANDING THAI CULTURE AND ITS IMPACT ON REQUIREMENTS ENGINEERING PROCESS MANAGEMENT DURING INFORMATION SYSTEMS DEVELOPMENT - Theerasak Thanasankit ,; Brian Corbitt , (Asian Academy of Management Journal, 2002)
This paper explores the impact of Thai culture on managing the decision making process in requirements engineering and contribution a better understand of its influence on the management of requirements engineering process. The paper illustrates the interaction of technology and culture and shows that rather than technology changing culture, culture can change the way technology is used. Thai culture is naturally inherent in Thai daily life and Thais bring that into their work practices. The concepts of power and uncertainty in Thai culture contribute toward hierarchical forms of communication and decision making process in Thailand, especially during requirements engineering, where information systems requirements need to be established for further development. The research shows that the decision making process in Thailand tends to take a much longer time, as every stage during requirements engineering needs to be reported to management for final decisions. The tall structure of Thai organisations also contributes to a bureaucratic, elongated decision-making process during information systems development. Understanding the influence of Thai culture on requirements engineering and information systems development will assist multinational information systems consulting organisations to select, adapt, better manage, or change requirements engineering process and information systems developments methodologies to work best with Thai organisations.